Features of adsorbed chemical elements and their isotopes distribution in iodine air filters FU-1500 of nuclear power plant - Neklyudov, I.M.; Dovbnya, A.N.; Dikiy, N.P.; Ledenyov, O.P.; Lyashko, Yu.V. (Вопросы атомной науки и техники, 2013)
The main aim of research is to investigate the physical features of spatial distribution of the adsorbed chemical elements and their isotopes in the granular filtering medium in the iodine air filters of the type of AU-1500 in the forced-exhaust ventilation at the nuclear power plant. The γ-activation analysis method is applied to accurately characterize the distribution of the adsorbed radioactive chemical elements and their isotopes in the granular filtering medium in the AU-1500 iodine air filter after its long term operation at the nuclear power plant. The typical spectrum of the detected chemical elements and their isotopes in the AU-1500 iodine air filter, which was exposed by the irradiation of bremsstrahlung γ-quantum producing by the accelerating electrons in the tantalum target, are obtained. The spatial distributions of the detected chemical element ¹²⁷I and some other chemical elements and their isotopes in the layer of absorber, which was made of the cylindrical coal granules of the type of SKT-3, in the AU-1500 iodine air filter are also researched. The possible influences by the standing wave of air pressure in the iodine air filter on the spatial distribution of the chemical elements and their isotopes in the iodine air filter are discussed. The comprehensive analysis of obtained research results on the distribution of the adsorbed chemical elements and their isotopes in the absorber of iodine air filter is performed. Головною метою було дослiдження особливостей розподiлення поглинених хiмiчних елементiв та їхнiх iзотопiв у гранульованому середовищi у йодному повiтряному фiльтрi типу AУ-1500 у притоковитягових системах на атомнiй електростанцiї. Метод γ-активацiйного аналiзу застосовано щоб охарактеризувати розподiлення поглинених хiмiчних елементiв та їхнiх iзотопiв у гранульованому фiльтовальному середовищi йодних повiтряних фiльтрiв типу AУ-1500 пiсля їх довгоготермiну роботи на атомнiй електростанцiї. Отриманi типовi спектри виявлених хiмiчних елементiв та їхнiх iзотопiв у повiтряному фiльтрi AУ-1500, зразки з якого опромiнювалися гальмовими γ-квантами, якi виникали при проходженнi прискорених електронiв через танталову мiшень. Просторове розподiлення йоду та деяких iнших хiмiчних елементiв та їхнiх iзотопiв у абсорберi, котрий був заповнений цилiндричними гранулами вугiлля типу СKT-3, у повiтряному фiльтрi AU-1500 було дослiджено. Можливий вплив стоячих коливань повiтряного тиску в йодному повiтряному фiльтру на просторове розпредiлення радiоактивних хiмiчних елементiв та їхнiх iзотопiв у йодному повiтряному фiльтрi було обговорено авторами. Зроблено всебiчний аналiз отриманих результатiв дослiдження просторового розподiлення хiмiчних елементiв та їхнiх iзотопiв у повiтряному фiльтрi. Главной целью работы было исследование особенностей, распределения адсорбированных химических элементов и их изотопов в гранулированной фильтрующей среде в йодных воздушных фильтрах типа АУ-1500 в системах приточно-вытяжной вентиляции на атомной электростанции. Использован метод γ-активационного анализа для точного изучения распределения адсорбированных химических элементов и их изотопов в гранулированной адсорбирующей среде в йодных воздушных фильтрах АУ-1500 после их долгосрочной работы на атомной электростанции. Получены типичные спектры обнаруженных химических элементов и их изотопов в йодном воздушном фильтре АУ-1500, образцы из которого облучались тормозными γ-квантами, возникавшими при прохождении ускоренных электронов через танталовую мишень. Найдено пространственное распределение йода и ряда других химических элементов и их изотопов в слое адсорбента, который состоял из цилиндрических угольных гранул СKT-3. Детально обсужден возможный механизм влияния стоячих колебаний давления воздуха в йодном воздушном фильтре на пространственное распределение поглощенных химических элементов и их изотопов. Выполнен всесторонний анализ полученных результатов исследования пространственного распределения адсорбированных радиоактивных химических элементов и их изотопов в адсорбенте йодного воздушного фильтра.